Drug use among street children and adolescents: what helps? Uso de drogas entre crianças e adolescentes em situação de rua: o que ajuda? - Yone Gonçalves de Moura; Zila M. Sanchez; Emérita S. Opaleye; Lucas Neiva-Silva; Silvia H. Koller; Ana R. Noto (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
The aim of this study was to investigate factors associated to frequent and heavy drug use among street children and adolescents aged 10 to 18 years. A sample of 2,807 street children and adolescents from the 27 Brazilian state capital cities was analyzed. A World Health Organization questionnaire for non-students was adapted for use in Brazil. Data analysis was performed using logistic regression and decision tree models. Factors inversely associated with frequent and heavy drug use were: being age nine to 11 years (OR = 0.1); school attendance (OR = 0.3); daily time (one to five hours) spent on the streets (OR = 0.3 and 0.4); not sleeping on the streets (OR = 0.4); being on the streets for less than one year (OR = 0.4); maintenance of some family bonds (OR = 0.5); presence on the streets of a family member (OR = 0.6); not suffering domestic violence (OR = 0.6); being female (OR = 0.8). All of these variables were significant at the p < 0.05 level. The findings suggest that being younger, having family bonds and engagement in school are important protective factors that affect drug use among this population and should be considered in the formulation of public policies. O objetivo do estudo foi verificar fatores associados ao uso frequente e pesado de drogas entre adolescentes em situação de rua no Brasil. Estudo transversal com amostra representativa nacional de 2.807 crianças e adolescentes (10-18 anos). Foi usado um questionário da Organização Mundial da Saúde adaptado para o Brasil e análise dos dados, modelo de regressão logística. Fatores inversamente associados ao uso frequente e pesado de drogas: faixa etária entre 9-11 anos (OR = 0,1); frequentar escola (OR = 0,3); permanecer entre 1 e 5 horas na rua (OR = 0,3 e 0,4); não dormir na rua (OR = 0,4); estar na rua há menos de um ano (OR = 0,4); manter algum vínculo familiar (OR = 0,5); permanecer na rua com algum membro da família (OR = 0,6); não ter sofrido violência doméstica (OR = 0,6); gênero feminino (OR = 0,8). Todas essas variáveis apresentaram p < 0,05. Os achados sugerem que ser mais jovem, ficar menos tempo na rua e manter vínculos com escola e família são importantes fatores de proteção para essa população quanto ao uso frequente e pesado de drogas. Esses são fatores importantes na formulação de políticas públicas para essa população.